Dampak Covid-19 Terhadap Kebiasaan Bermain Gadget Pada Anak Usia Sekolah - Handoko Handoko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The corona virus which hits Indonesia brings about a great impact on education. The learning system that is usually carried out in a face-to-face interaction changes with an online system. The online learning system which requires children to use gadgets is quite to have a big impact on children's development. The former children’s habit who were not using gadgets began to change for reasons of learning. After learning is complete, children play gadgets. The resulting impact is a decrease in interest and enthusiasm for learning. This must be controlled by parents and teachers to restore students‘ interest and enthusiasm for learning, especially of a school age students. This research was a qualitative research employing interview and observation methods. The research sample was elementary school age children who are in Seputih Banyak District, Central Lampung. The results point out that during the COVID-19 pandemic, children‘s playing habits increased. It is a common situation for school-age children to spend only a few moments studying, but spending a long time playing gadgets. A control from parents is very necessary so that school-age children can use gadgets only in line with their needs.